DEATH PENALTY EXECUTION AND THE RIGHT TO LIFE IN PERSPECTIVE OF HUMAN RIGHTS, 1945 CONSTITUTION OF THE REPUBLIC OF INDONESIA, AND INDONESIAN LAW - Oksidelfa Yanto (Yustisia, 2016)
AbstractThe execution of Death penalty in Indonesia is based on the court verdict that has had a permanent legal power. Only through the court ruling a man can be executed a death penalty upon the guilty alleged at him/her. The death penalty application in Indonesia is provided in the positive law with specific or general nature. As a country having the most verdicts with the capital punishment, either to its local citizen or to the foreign citizen who commits any offenders in the jurisdiction of Republic of Indonesia, triggering the existing of pro and contra stance on the capital punishment execution. The opposing stance based its argument on the human rights perspective, affirming that the capital punishment can be categorized as a form of savage and inhuman punishment and is in the contrary with the constitution. While the stance supporting the capital punishment execution is based on the argumentation that the perpetrator must be avenged in compliance with his/her commit, in order to give a deterrent effect for others who want to commit similar offense.    Nevertheless as a matter of fact, there are still many similar offense occurred though capital punishment has been implemented.